ANALISIS KESULITAN SISWA SMP DALAM MENYELESAIKAN SOAL CERITA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Gida Kadarisma; Luvy Sylviana Zhanthy; Rindiani Rindiani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to analyze the difficulties of students at SMP IT in Cimahi in solving story problems on the material for the Two Variable Linear Equation System (SPLDV). This study used descriptive qualitative method. The subject in this study was to take a sample of 10 students from class VIII. Data was obtained by testing written test questions in the form of essays that refer to the indicators that have been set in the learning instrument. From the data analysis, it is known the students' difficulties. The difficulties experienced by students include students having difficulty converting story questions into mathematical models, difficulties at the stage of solving problems in the elimination method, substituting one of the variables that were previously found, and changing the replacement value of the variable that has been found into the sentence asked in this stage draw conclusions.